Women of Rembang Nurturing Kendeng Water Springs: a Study of the Impact of Mining to Women’s SRHR - Tommy Apriando (Yayasan Jurnal Perempuan, 2015)
This paper investigates the fulfillment of SRHR in Rembang during the protest against cement mining in Kendeng Mount. This paper concludes that women’s SRHR are being denied by the government as the access to water and food will be in jeopardy. The interviews took place in Tegaldowo Village and Timbrangan Village Rembang. The arrival of cement mining has threatened the livelihood of the forest, the community, and water capture.